Turkish version of the Tilburg Frailty Indicator - Topcu Y (Clinical Interventions in Aging, 2019)
Yildiray Topcu, Fatih Tufan, Cihan Kilic Department of Geriatrics, Istanbul School of Medicine, Istanbul University, Istanbul, Turkey Background: Recently frailty has drawn significant interest as an important predictor of several clinically relevant outcomes. There is no widely accepted instrument for the assessment of frailty and most of the current ones evaluate only physical features. The Tilburg Frailty Indicator (TFI) is a valid and reliable instrument which enables multidimensional assessment of frailty. We aimed to adapt and evaluate the Turkish version of the TFI.Methods: We translated and culturally adapted the English version of the TFI into Turkish using standard guidelines. We enrolled consecutive patients who were 70 years old or older and were admitted to our outpatient geriatrics clinic. We used Cronbach’s alpha values to evaluate the internal consistency and also assessed inter-observer and test–retest variability using intraclass correlation coefficient (ICC).Results: The Cronbach’s alpha reliability coefficients of the instrument ranged from 0.65 to 0.72 and item-total correlation ranged between -0.05 and 0.57. There was a good agreement between two assessments (ICC=0.99) and between two observers (ICC=0.99).Conclusion: We have shown the reliability of the Turkish version of the TFI as a tool to evaluate frailty in a multidimensional manner among the Turkish outpatient population. Keywords: Tilburg Frailty Indicator, Turkish version, internal consistency, validity, older individuals, aging, frailty, multidimensional assessment, psychosocial factors, validation study, cultural adaptation, older adults